Dwelling on the Borders: Self. Text and World - Flood, Gavin (Temenos, 2008)
In spite of secularist predictions, religion on a global scale has not gone away and shows little sign of dimnishing. Within the context of the renewal of interest in religion and the assertion of religion in the public realm, I seek in this article to explore the ways in which the self has been (and continues to be) formed in religious traditions. Drawing on substantive examples from my work on textual traditions in India and Europe, the article argues that 'religious reading' is central to the formation of religious traditions and the formation of the religious person, and that this has an impact upon discourse in the public realm. The process of religious reading itself occurs in a borderland between text and world and between self and world. Through 'religious reading', or more precisely textual reception, we can understand the ways in which forms of inwardness are constructed in tradition-specific ways and such inwardness too has an impact on public discourse. I therefore attempt to examine three traditional borderlands - between inwardness and externality, between text and world, and between private religion and public governance - in the light of religious reading.